Guidance for Adolescents from the Perspective of Qur'anic Education - Mustakim, Muh; Farida, Fitria Nur; Imron, Ali; Rosyidin, Fachry Ali (Journal of Islamic Education and Ethics, 2026)
Adolescence is a transitional phase from childhood to adulthood marked by identity exploration, a strong need for social acceptance, and the development of abstract thinking. When this developmental period is not properly guided, adolescents may face challenges that affect themselves, their families, and society. This study examines adolescent education from the perspective of Qur’anic education using qualitative methods and a literature review approach. The findings indicate that adolescent education should aim to develop cognitive, social, and emotional competencies required for a successful transition to adulthood, enabling adolescents to meet life’s demands and contribute positively to society. From a Qur’anic perspective, adolescent development requires a comprehensive and integrative educational approach involving families, schools, and the broader community to create a holistic educational ecosystem. This approach upholds local religious and cultural values while remaining responsive to global developments. The study emphasizes that responsibility for adolescent education is shared among multiple stakeholders rather than being centered solely on parents. The findings also highlight the importance of character formation through monotheistic values, purification of the soul, exemplary conduct, and the cultivation of social awareness and responsibility. Strengthening faith, devotion to parents, and noble character forms the foundational basis of adolescent education, alongside the development of independence and social responsibility. Overall, the study proposes a Qur’an-based framework for adolescent development that includes moral formation, intellectual and spiritual growth, enhanced social responsibility, and the development of independence and leadership capacities.